(untitled) (Communications in Computational Physics, 2020)
Ru-Shan Wu is a special scientist who has made tremendous contributions in many fields of geophysics that he has worked on and has had strong impact on several generations of scientists throughout the world. He is appreciated for his contributions to science and for his generous, outgoing and happy personality that make him a role model for those who follow in his footsteps. Ru-Shan has sustained high-quality scientific output over the course of his long career. His work is widely recognized for its value and creativity. He has keen insight into the underlying physics of wave propagation and he continues to successfully transform that insight into fundamental advances in our understanding of wave propagation and imaging.